2010
DOI: 10.1371/journal.pone.0015015
|View full text |Cite
|
Sign up to set email alerts
|

Evolution and Mechanism of Spectral Tuning of Blue-Absorbing Visual Pigments in Butterflies

Abstract: The eyes of flower-visiting butterflies are often spectrally highly complex with multiple opsin genes generated by gene duplication, providing an interesting system for a comparative study of color vision. The Small White butterfly, Pieris rapae, has duplicated blue opsins, PrB and PrV, which are expressed in the blue (λ max = 453 nm) and violet receptors (λ max = 425 nm), respectively. To reveal accurate absorption profiles and the molecular basis of the spectral tuning of these visual pigments, we successful… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
70
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(73 citation statements)
references
References 30 publications
3
70
0
Order By: Relevance
“…Wakakuwa et al showed that amino acid substitutions at sites 116 and 177 are crucial for spectral tuning in the Pr B and Pr V pigments. 24 As already mentioned before, within 5.0 Å environment of the retinal, seven sites in Pr B opsin and three sites in Pr V opsin differ in their identity compared to the squid opsin. However, due to difference in their polarity, only sites 116 and 177 were mutated in the experimental study.…”
Section: Spectral Tuning In Small White Butterfliesmentioning
confidence: 73%
See 3 more Smart Citations
“…Wakakuwa et al showed that amino acid substitutions at sites 116 and 177 are crucial for spectral tuning in the Pr B and Pr V pigments. 24 As already mentioned before, within 5.0 Å environment of the retinal, seven sites in Pr B opsin and three sites in Pr V opsin differ in their identity compared to the squid opsin. However, due to difference in their polarity, only sites 116 and 177 were mutated in the experimental study.…”
Section: Spectral Tuning In Small White Butterfliesmentioning
confidence: 73%
“…In contrast, mutation of serine with alanine at site 116 (S116A) induces a red shift of 10 nm in agreement with experimental findings. 24 Apparently, only half of the blue shift (20 nm) induced by S116 in Pr B is recovered with A116 in Pr V. The calculated spectral shifts are non-additive as introduction of all three mutants decreases the λ max by only 7 nm.…”
Section: Spectral Tuning In Small White Butterfliesmentioning
confidence: 85%
See 2 more Smart Citations
“…In the visual cells of invertebrates, Gq-coupled opsin-based pigments light dependently activate a Gq-type G protein (Terakita et al 1993 ;Koyanagi and Terakita 2008 ), which results in the depolarization of these cells (Yau and Hardie 2009 We successfully obtained several Gq-coupled opsin-based pigments, which had different wavelength sensitivities, by expressing these opsins in cultured cells. These included UV-and blue-sensitive honeybee opsin-based pigments , blue-and violet-sensitive butterfl y opsin-based pigments (Wakakuwa et al 2010 ), green-sensitive spider opsin-based pigment (Nagata et al 2012 ), and blue-sensitive amphioxus melanopsin (Koyanagi et al 2005 ).…”
Section: Spider Opsin: Gq-coupled Opsinmentioning
confidence: 99%